The impact of information technology on global organizational strategy, structure, process, and performance. - Tan, Michael Sian Teck. (2009)
Despite substantial and bold claims of what information technology (IT) can do to transform organizations in conformance with current business imperatives, there is relatively little empirical evidence that illustrate when, how, or why IT enables these transformations.